(untitled) (AYUSHDHARA, 2018)
Ayurveda has a holistic approach and includes all the factors which are accessory in the determination of health. For the prevention of various diseases, selection of a preventive and curative regime is primarily based on phenotypic assessment of a person which includes one’s body constitution termed ‘Prakriti’. Deha Prakriti is represented by a description of the Physique, Physiology & psychological make-up of an individual. Prakriti is a consequence of the relative proportion of three physiological entities (Tridoshas), Vata, Pitta and Kapha which are genetically determined & is decided at the time of conception and is likely to be influenced by a variety of environmental factors to some extent. Prakriti of a person is quite capable of providing a fair indication of physiological strengths and weaknesses, mental tendencies and susceptibility to illness of various types. Knowing Prakriti is a wonderful tool for understanding ones and others, and it also aids a person in making appropriate dietary and lifestyle choices for maintaining health. From a practitioners view, it is used in the selection of medicines and other therapies for a particular patient as well as in selecting appropriate dosage of the drugs. So Prakriti assessment can be used as best way for the prognosis and prevention of various diseases.